The effect of gamma radiation on seed germination of barley (Hordeum vulgare L.) - Ludvik ROZMAN (Acta Agriculturae Slovenica)
The aim of the study was to determine the effect of gamma radiation on barley (Hordeum vulgare L.) seed germination and changes of seed viability associated with aging. The seed samples of the variety 'Astor' were irradiated at the Jožef Štefan Institute, in the Reactor Centre at Podgorica near Ljubljana, in 2006. The samples were irradiated with three different doses: 0.1, 0.2 and 0.4 kGy. After the irradiation, the seeds were stored in a refrigerator at 4 °C. The percentage of seed germination was tested each year after irradiation until 2014, except in the second and the third year. The experiments were based on the Latin square design with 4 replications of each treatment, and were conducted in a greenhouse under controlled temperature at 20 °C. In all years, the samples irradiated with the highest dose (0.4 kGy) exhibited a significantly lower percentage of germination. The germination rate of the samples irradiated with 0.2 and 0.4 kGy decreased significantly with aging, when compared to the control and the samples irradiated with 0.1 kGy. In all years of testing, the percentage of germination of seeds irradiated with 0.1 kGy did not differ from the control, and in the fifth year after irradiation, it was even significantly higher than the control.